On the Role of Testosterone in Anxiety-Like Behavior Across Life in Experimental Rodents - Domonkos, Emese; Hodosy, Július; Ostatníková, Daniela; Celec, Peter (Frontiers in Endocrinology, 2018)
Testosterone affects brain functions and might explain some of the observed behavioral sex differences. Animal models may help in elucidating the possible involvement of sex hormones in these sex differences.. The effects of testosterone have been intensively investigated, especially in anxiety models. Numerous experiments have brought inconsistent results with either anxiolytic or anxiogenic effects. Besides methodological variations, contradictory findings might be explained by the divergent metabolism of testosterone and its recognition by neurons during prenatal and postnatal development. Gonadectomy and subsequent supplementation have been used to study the role of sex hormones. However, the variable duration of hypogonadism might affect the outcomes and the effect of long-term androgen deficiency is understudied. Testosterone can be metabolized to dihydrotestosterone strengthening the androgen signaling, but also to estradiol converting the androgen to estrogen activity. Moreover, some metabolites of testosterone can modulate γ-aminobutyric acid and serotonergic neurotransmission. Here we review the currently available experimental data in experimental rodents on the effects of endogenous and exogenous testosterone on anxiety during development. Based on the experimental results, females are generally less anxious than males from puberty to middle-age. The anxiety-like behavior of females and males is likely influenced by early organizational effects, but might be modified by activational effects of testosterone and its metabolites. The effects of sex hormones leading to anxiogenesis or anxiolysis depend on factors affecting hormonal status including age. The biological and several technical issues make the study of effects of testosterone on anxiety very complex and should be taken into account when interpreting experimental results.